Influência de inseticidas e acaricidas no crescimento de plântulas de cacaueiro (Theobroma cacao L.) - Smith F, Enrique; Silva, Pedrito (Revista Ceres, 2025)
The effects of foliarapplications of different commercial insecticides andacaricides on the growth of 3-months old cacao seedlings were investigated under greenhouse conditions. The pesticides were applied either as a dustor a sprayat different concentrations.